Synthesis and characterisation study on the structure and property of biodegradable copolyester of PET/ɛCL; PET/PCL; PET/PGA - Wong, Yong Xing. (2011)
In recent years, the production of PET bottles for packaging purposes has been increasing at a very fast rate. Hence, recycling of PET waste bottles has been a major concern over these few years as PET takes hundreds of years to degrade by landfill method. Although several chemical recycling methods were proposed, many of them were at the research phase as the cost of recycling and eco-friendly recycling are important in the industrial aspect. With the mindset of improving the ease of recycling and at the same time being eco-friendly, a novel biodegradable PET bottle is being proposed. This concept focuses on the copolymerisation of PET with biodegradable polymer or monomer. Through this copolymerization, long PET chains could be broken down into smaller ones with chains of biodegradable polymer or monomer in between them.